Proteomic Analysis of Plasma-Derived Extracellular Vesicles From Mice With Echinococcus granulosus at Different Infection Stages and Their Immunomodulatory Functions - Shi, Chunli; Zhou, Xiaojing; Yang, Wenjuan; Wu, Jianwen; Bai, Min; Zhang, Ying; Zhao, Wei; Yang, Hui; Nagai, Atsushi; Yin, Mei; Gao, Xiaoping; Ding, Shuqin; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The globally distributed cystic echinococcosis (CE) is caused by the larval stage of Echinococcus granulosus (E. granulosus), a cosmopolitan and zoonotic disease with potentially life-threatening complications in humans. The emerging roles for extracellular vesicles (EVs) in parasitic infection include transferring proteins and modifying host cell gene expression to modulate host immune responses. Few studies focused on the host-derived EVs and its protein profiles. We focused on the EVs from mouse infected with E. granulosus at different stages. ExoQuick kit was used for isolating EVs from mouse plasma and ExoEasy Maxi kit was used for isolating protoscolex culture supernatant (PCS) and hydatid cyst fluid (HCF). Firstly, EVs were characterized by transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA) and immunoblot. Secondly, the proteins of plasma EVs were identified using liquid chromatography-tandem mass spectrometry (LC–MS/MS). The resulting LC–MS/MS data were processed using Maxquant search engine (v 1.5.2.8). Tandem mass spectra were researched against the mice and E. granulosus proteins database in the NCBI. The differentially expressed proteins are performed by proteomic label-free quantitative analysis and bioinformatics. Thirdly, in vitro experiment, the results of co-culture of plasma EVs and spleen mononuclear cells showed that 7W-EVs can increase the relative abundance of regulatory T (Treg) cells and IL-10. We further verified that EVs can be internalized by CD4+ and CD8+ T cells, B cells, and myeloid-derived suppressor cells (MDSC). These results implied host-derived EVs are multidirectional immune modulators. The findings can contribute to a better understanding of the role of host-derived EVs which are the optimal vehicle to transfer important cargo into host immune system. In addition, we have found several important proteins associated with E. granulosus and identified in infected mouse plasma at different stages. Furthermore, our study further highlighted the proteomics and immunological function of EVs from mouse infected with E. granulosus protoscoleces at different infection stages. We have laid a solid foundation for the role of EVs in cystic echinococcosis in the future research and supplemented a unique dataset for this E. granulosus.